Synthesis and biological activity of the pinostrobin oxime complex compounds with some d-metals - Mashentseva, A. A.; Seytembetov, T. S.; Adekenov, S. M.; Tuleuov, B. I.; Loiko, O. P.; Khalitova, A. I. (Russian Journal of General Chemistry, 2011)
The process of the complex formation by the natural flavonoid pinostrobin (5-hydroxy-7-methoxyflavonone) oxime with the Cu(II) and Fe(III) ions in a water-ethanol medium was investigated. The metal: ligand ratio in the complex was determined by the saturation method. The results of the analysis of IR spectra and the data of mass-spectrometric studies of the structure of the obtained complex compounds are reported. The antiviral activity of the synthesized complexes with respect to the human immunodeficiency virus HIV-1 IIIB and HIV-2 ROD strains was studied. The antioxidant activity of the complexes, as well as the parent pinostrobin oxime ligand, was evaluated with respect to the diphenylpicrylhydrazyl (DPPH) radical and the 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical cation.